Thromboelastography Parameters do not Discriminate for Thrombotic Events in Hospitalized Patients With COVID-19. (May 2023) - Kartiko, Susan; Koizumi, Naoru; Yamane, David; Sarani, Babak; Siddique, Abu B.; Levine, Andrea R.; Jackson, Amanda M.; Wieruszewski, Patrick M.; Smischney, Nathan J.; Khanna, Ashish K.; Chow, Jonathan H.; ,
Background: Coronavirus disease 2019 (COVID-19) is associated with a prothrombotic state; leading to multiple sequelae. We sought to detect whether thromboelastography (TEG) parameters would be able to detect thromboembolic events in patients hospitalized with COVID-19. Methods: We performed a retrospective multicenter case–control study of the Collaborative Research to Understand the Sequelae of Harm in COVID (CRUSH COVID) registry of 8 tertiary care level hospitals in the United States (US). This registry contains adult patients with COVID-19 hospitalized between March 2020 and September 2020. Results: A total of 277 hospitalized COVID-19 patients were analyzed to determine whether conventional coagulation TEG parameters were associated with venous thromboembolic (VTE) and thrombotic events during hospitalization. A clotting index (CI) >3 was present in 45.8% of the population, consistent with a hypercoagulable state. Eighty-three percent of the patients had clot lysis at 30 min (LY30) = 0, consistent with fibrinolysis shutdown, with a median of 0.1%. We did not find TEG parameters (LY30 area under the receiver operating characteristic [ROC] curve [AUC] = 0.55, 95% CI: 0.44-0.65, P value = .32; alpha angle [α] AUC = 0.58, 95% CI: 0.47-0.69, P value = .17; K time AUC = 0.58, 95% CI: 0.46-0.69, P value = .67; maximum amplitude (MA) AUC = 0.54, 95% CI: 0.44-0.64, P value = .47; reaction time [R time] AUC = 0.53, 95% CI: 0.42-0.65, P value = .70) to be a good discriminator for VTE. We also did not find TEG parameters (LY30 AUC = 0.51, 95% CI: 0.42-0.60, P value = .84; R time AUC = 0.57, 95%CI: 0.48-0.67, P value .07; α AUC = 0.59, 95%CI: 0.51-0.68, P value = .02; K time AUC = 0.62, 95% CI: 0.53-0.70, P value = .07; MA AUC = 0.65, 95% CI: 0.57-0.74, P value < .01) to be a good discriminator for thrombotic events. Conclusions: In this retrospective multicenter cohort study, TEG in COVID-19 hospitalized patients may indicate a hypercoagulable state, however, its use in detecting VTE or thrombotic events is limited in this population.